Clinicopathologic Characteristics and Impact of Oophorectomy for Ovarian Metastases from Colorectal Cancer. (7th February 2020) - Ursem, Carling; Zhou, Margaret; Paciorek, Alan; Atreya, Chloe E.; Ko, Andrew H.; Venook, Alan; Zhang, Li; Van Loon, Katherine
Abstract: Background: As survival with metastatic colorectal cancer (CRC) and imaging modalities improve, detection of ovarian metastases may be increasing. The ovary may serve as a sanctuary site for malignant cells; however, there is a paucity of data regarding the role for oophorectomy. Methods: This is a single‐institution retrospective study of patients with CRC with ovarian metastases from 2009 to 2017. We evaluated patient, disease, and treatment related factors associated with overall survival (OS) from initial diagnosis of metastatic CRC. Results: Of 108 patients assessed, the median age was 50, 19% had localized disease at initial presentation, 64% had ovarian metastases at initial CRC diagnosis, and 77% underwent oophorectomy. Median OS was 29.6 months across all patients, and it was 36.7 months in patients who underwent oophorectomy versus 25.0 months in patients who did not (hazard ratio [HR] 0.54). In multivariate analysis, the effect of oophorectomy on OS suggested protection but was not statistically significant (HR 0.57). Resection of primary tumor was performed in 71% of patients, which was independently associated with improved OS (HR 0.21). Twelve patients (11%) remained alive at 5 years after diagnosis of metastatic disease. Conclusion: Although it has been previously reported that patients with CRC with ovarian metastases have poor prognosis, the median OS for this cohort was comparable to existing OS data for patients with metastatic CRC. In patients treated with chemotherapy, we did not find the ovarian metastasis to frequently serve as a sanctuary site of disease. However, we found that in carefully selected patients, oophorectomy may confer a survival benefit. Implications for Practice: In colorectal cancer (CRC) ovarian metastasis is not necessarily associated with worse prognosis than metastasis to other sites. In carefully selected patients with ovarian metastases from CRC, oophorectomy may confer a survival benefit. Specifically, development of ovarian metastasis early in the disease course, resection of the primary tumor, and limited extraovarian metastatic disease are clinical features that are potentially associated with benefit from oophorectomy. A subset of patients with ovarian metastasis from CRC have potential to become long‐term survivors (>5 years). Abstract : In patients with colorectal cancer, the presence of ovarian metastases has previously been thought to portend a worse prognosis than other sites of metastatic disease. This article focuses on outcomes in the modern chemotherapy era and the role of oophorectomy and selection of patients who are likely to benefit.